Maho-chan-chi = Maho-chan's lovely home. (Mito : Contemporary Art Center Art Tower Mito Mito-shi, 2004)
An exhibition presented by the father-mother-daughter trio of artists, Shinzo Shimao (b. 1948, novelist and photographer), Tokuko Ushioda (b. 1940, photographer), and Maho Shimao (b. 1978, cartoonist).
Also exhibited at Art Tower Mito this time are miscellaneous household items the Shimaos picked up while in China, as they often go there on vacation, along with photographs they took there. The exhibition is based on their co-authored book, "Guide to Common Chinese Living."
Meanwhile, Tokuko Ushioda concentrates on taking pictures of various objects to evoke people's daily lives. For example, her "ICE BOX" series portrays refrigerators actually in use at various households, and other series feature photographs of such things as old books and creative hats.
Shinzo Shimao - the son of the famous novelist, Toshio Shimao (1917-86), who was renowned for such works as "The Sting of Death," a collection of short stories - brings his delicate perspective to events closely related to his own life. His works include "Maho-chan," a series of photographs of his daughter when she was little, and "Searching for a Lost Time," snapshots and essays from a trip to his native Amami Islands, situated between Okinawa and Kyushu.
Their daughter, Maho Shimao, set off a quiet boom seven years ago with her popular comic book, "Goriko, High School Girl," and has now turned her attention to formative art works as well as visual ones.
Japans
Exhibition. Maho-chan-chi = Maho-chan's lovely home. Contemporary Art Center Art Tower Mito Mito-shi. 23.10.2004 - 10.01.2005
Keywords: Shimao, Shinzo; Ushioda, Tokuko; Shimao, Maho